Examination of the performance and scalability of a web application in a reactive and imperative approach using the Spring Framework - Lis, Karol; Smołka, Jakub (Journal of Computer Sciences Institute, 2024)
The purpose of this paper was to test the performance and scalability of a web application written in reactive and imperative approaches using the Spring Framework, in order to understand the differences between these approaches and choose the technology that best meets the requirements and provides optimal performance. Two test applications were compared in terms of query processing times and CPU/RAM usage. The effect of Api Gateway microservices on application performance was analyzed. The tests showed that the reactive application processed I/O operations faster, used less RAM but more CPU. The imperative approach was faster for transactional operations performed sequentially. The reactive variant reacted with less latency to the presence of Api Gateway than the imperative approach.